High-dose chemotherapy as initial salvage chemotherapy in patients with relapsed or refractory testicular cancer: a systematic review and meta-analysis - Briones, Juan; Diaz, Pamela; Nicholson, Brian D. (Frontiers in Oncology, 2024)
BackgroundThe role of high-dose chemotherapy followed by autologous hematopoietic cell transplantation in the management of patients with relapsed/refractory germ-cell tumors has not been established in prospective studies. Our aim was to estimate the benefits and harm of this treatment in men with relapsed/refractory germ-cell tumors.MethodsElectronic databases, conference proceedings, and trial registers until April 30, 2023, were searched. Randomized and non-randomized prospective controlled trials were included. Risk of bias assessments were performed using either RoB2 or ROBINS-I tools. The certainty of evidence was assessed using the Grading of Recommendations, Assessment, Development, and Evaluations (GRADE) approach. Time-to-event data were analyzed using the hazard ratio. The primary outcome was overall survival, and a meta-analysis was not conducted to assess it because non-randomized trials were judged to have a critical risk of bias. Categorical data were analyzed using a risk ratio. All results are presented with the corresponding 95% confidence interval.ResultsFour out of 3,824 records met the inclusion criteria, and three out of four were used to assess primary and secondary outcomes. Based on the IT94 study (N = 263 participants), single high-dose chemotherapy followed by autologous hematopoietic cell transplantation may have little to no effect on overall survival [hazard ratio (HR) 0.98, 95%CI 0.68 to 1.42; p = 0.916]. Non-randomized trials (N = 43 participants) showed contrasting results, which may be explained by the number of cycles of high-dose chemotherapy administered in each study. Regarding secondary outcomes, information was only provided for event-free survival, response rate, and acute toxicities.ConclusionsBased on prospective data, there is insufficient evidence to support or refute the proposal that high-dose chemotherapy with autologous hematopoietic cell transplantation improves survival in men with relapsed/refractory germ-cell tumors. If this treatment is considered essential, the choice should be made by experienced clinicians at high-volume cancer centers.